FAKTOR PENYEBAB KESULITAN BELAJAR WARGA BELAJAR PROGRAM PENDIDIKAN KESETARAAN DALAM MENGIKUTI PROSES PEMBELAJARAN DI PKBM KAK SETO PEKANBARU - Ramadhani, Dwi Cahya; Wilson, Wilson; Jas, Jasfar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine the factors causing the learning difficulties of citizens learning equality education program in following the learning process in PKBM KAK SETO PEKANBARU. The formulation of the problem in this research is whether the factors causing the learning difficulties of citizens to study the equivalency education program in following the learning process in PKBM KAK SETO PEKANBARU. The population in this study as many as 30 residents learn. the researchers used the saturated samples so that all the population in the sample made as many as 30 people studying in PKBM KAK SETO PEKANBARU, and 20 people for trials in Learning Activity Center (SKB) Pekanbaru City. The type of this research is descriptive with quantitative approach. The instrument of data collection is questionnaire with 38 statement and after test stay 35 valid statement to be made in research instrument. Data analysis through quantitative descriptive analysis. The findings of the research indicate that the acquisition of the percentage of the sums of Strongly Agree (SS) with Agree (S) on all indicators are (1) internal factors and (2) external factors of 59.05% or can be said to be moderate. This shows that the surrounding environmental factors and factors from within themselves are quite influential on the learning difficulties of learning people in following the learning process in PKBM KAK SETO PEKANBARU.Keywords : Learning Difficulties, Students of Learning, Equality Education